Incisor Malocclusion Using Cut-out Method And Convolutional Neural Network - Muhamad Farhin Harun; Azurah A Samah; Muhammad Imran Ahmad Shabuli; Hairudin Abdul Majid; Haslina Hashim; Nor Azman Ismail; Syiral Mastura Abdullah; Aspalilah Alias (HH Publisher, 2024)
Indexed by Scopus